Association of stroke risk biomarkers with stroke symptoms: the Reasons for Geographic and Racial Differences in Stroke cohort. (9th December 2016) - Landry, K. K.; Alexander, K. S.; Zakai, N. A.; Judd, S. E.; Kleindorfer, D. O.; Howard, V. J.; Howard, G.; Cushman, M.
Abstract : Essentials Stroke symptom history predicts future stroke and may indicate prior unrecognized stroke. We studied associations of stroke symptoms with stroke risk biomarkers. Several stroke risk biomarkers were independently associated with stroke symptom history. Findings support a hypothesis that stroke symptoms may represent unrecognized stroke. Summary: Background: History of stroke symptoms in the absence of prior diagnosed stroke or transient ischemic attack (TIA) is associated with future stroke risk, as are biomarkers of inflammation, cardiac function and hemostasis. Objective: To better elucidate the pathobiology of stroke symptoms, we studied associations of these biomarkers with history of stroke symptoms. Methods: The Reasons for Geographic and Racial Differences in Stroke (REGARDS) cohort enrolled 30 239 black and white Americans age 45 years and older in 2003–7. In cross‐sectional analyses in a random sample of 960 participants without prior stroke or TIA, levels of N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP), fibrinogen, factor VIII (FVIII), factor XI (FXI), C‐reactive protein (CRP) and D‐dimer were studied in relation to self‐reported history of six sudden onset stroke symptoms. Results: There were 190 participants with at least one stroke symptom and 770 without. Adjusting for age, race, sex and stroke risk factors, NT‐proBNP, FXI, CRP and D‐dimer in the top vs. bottom quartile were associated with prevalent stroke symptoms with odds ratios 2.69 (95% confidence interval [CI], 1.45–4.98), 1.65 (95% CI, 1.00–2.73), 2.21 (95% CI, 1.32–3.71) and 2.14 (95% CI, 1.22–3.75), respectively. Conclusions: Strong associations of stroke risk biomarkers with stroke symptoms in persons without a clinical history of cerebrovascular disease support a hypothesis that some of these stroke symptoms represent unrecognized cerebrovascular disease. Future work is needed to determine whether these biomarkers identify persons with stroke symptoms who have a particularly high stroke risk.